Quantitative Analysis of the Proteome and the Succinylome in the Thyroid Tissue of High-Fat Diet-Induced Hypothyroxinemia in Rats - Baoxiang Hu; Meng Zhao; Dandan Luo; Chunxiao Yu; Shanshan Shao; Lifang Zhao; Yashuang Yang; Xiaohan Zhang; Jiajun Zhao; Ling Gao (International Journal of Endocrinology)
Hypothyroidism is a common disease, and its molecular mechanism still needs further investigation. Lysine succinylation is found to be involved in various metabolic processes associated with hypothyroidism. We performed quantitative analysis on lysine succinylome in thyroids of rats with hypothyroxinemia, which was induced through the administration of a high-fat diet. Overall, 129 differentially expressed proteins were quantified. Downregulated proteins were enriched in the thyroid hormone synthesis and thyroid hormone signaling pathways and were mainly localized in the mitochondria. In addition, 172 lysine succinylation sites on 104 proteins were obviously changed. Decreased succinylated proteins were involved in diverse metabolic pathways and were primarily localized in mitochondria. Finally, the mitochondrial oxygen consumption rates of human normal thyroid epithelial cells were measured to further verify the role of lysine succinylation. The mitochondrial oxygen consumption rates were markedly blunted in the cells treated with palmitic acid (all p<0.05), and the changes were reversed when the cells were treated with palmitic acid and desuccinylase inhibitor together (all p<0.05). Thus, we theorize that the thyroid differentially expressed proteins and changed succinylation levels played potential roles in the mitochondria-mediated energy metabolism in the high-fat diet-induced hypothyroxinemia rat model.